(NvENA I MUZA(B: [(NbIOGRAFIQ(B] /s - (NwASILXEWA(B, (NlARISA nIKOLAEWNAs ((NmOSKWA(B: s (N|KSMO(B-(NpRESS(B,s, 2001)
(NiZWESTNAQ PO\TESSA(B, (NPISATELXNICA(B, (NPUBLICIST(B, (NDRAMATURG(B, (NPEREWOD^IK(B, (NAWTOR BOLEE (B25 (NKNIG(B, (NIZDANNYH W rOSSII I ZA RUBEVOM(B, (NW TOM ^ISLE MIROWYH BESTSELLEROW (B"(NkREMLEWSKIE VENY(B" (NI (B"(NdETI kREMLQ(B", (NISTORIKO(B-(NPUBLICISTI^ESKOGO ISSLEDOWANIQ (B"(NvENY RUSSKOJ KORONY(B", (NKNIGI(B-(NALXBOMA (B"(NdU[A mOSKWY(B", (NPREDLAGAET ISTORIKO(B-(NPUBLICISTI^ESKU@ RABOTU (B"(NvENA I MUZA(B". (Nw NEJ RE^X IDET O TAJNOJ I ZAGADO^NOJ L@BWI aLEKSANDRA sERGEEWI^A pU[KINA(B, (NKOTORU@ ON T]ATELXNO SKRYWAL I PRONES ^EREZ WS@ VIZNX(B.s
rus
Keywords: (NmEMUARY(B, (NBIOGRAFIIs; (NsTIHOTWORENIQs; (NpISXMAs -- (NsTATXIs